Analytical solution of mixed boundary value problems using the displacement potential approach for the case of plane stress and plane strain conditions - Nath, S. K. Deb (Zielona Góra: Uniwersytet Zielonogórski)
Two elastic plate problems made of duralumin are solved analytically using the displacement potential approach for the case of plane strain and plane stress conditions. Firstly, a one end fixed plate is considered in which the rest of the edges are stiffened and a uniform load is applied to the opposite end of the fixed end. Secondly, a plate is considered in which all of the edges are stiffened and a uniform tension is applied at its both ends. Solutions to both of the problems are presented for the case of plane stress and plane strain conditions. The effects of plane stress and plane strain conditions on the solutions are explained.
Keywords: analytical solution; displacement potential approach; plane stress and plane strain conditions; mixed boundary value problems